ANALISIS PENGARUH MOTIVASI DAN PENGARUHNYA TERHADAP PERILAKU ANGGOTA KEMITRAAN USAHA AYAM BROILER DI KABUPATEN GROBOGAN - Marry Widyaningrum; Dyah Mardiningsih; Warsono Sarengat (Universitas Wahid Hasyim, 2017)
A research dedicated to understand just what exactly motivate breeders and its influences (knowledge, conduct and skills) on chicken farming in Grobogan District. Data in this research are collected through observation and interview with questionnaire, including the primary data.Methods used are quantitative and qualitative. Testing analysis is done by using a computer program called Statistic Package for Social Seience (SPSS 16) with a simple linear regression test to find out breeders’ motivation and behavioral effects on the broiler chicken business. Based on the research in Grobogan District, it can be concluded as such: geographically, Grobogan District is suitable for chicken farming due to the abundance of food resources especially corn. Motivation level of the breeders is relatively high. The breeders’ behavior which includes knowledge, conduct and skills is categorized as also high. The result of the simple linear regression test shows that motivation is influenced by behavior and knowledge, while conduct and skills do not visibly affect the motivational aspect of the breeders. Keywords: Breeders, Motivation, Behavior.